Immunogenicity trends 1 and 3 months after second BNT162B2 vaccination among healthcare workers in Israel. (March 2022) - Shachor-Meyouhas, Yael; Hussein, Khetam; Dabaja-Younis, Halima; Szwarcwort-Cohen, Moran; Almog, Ronit; Weissman, Avi; Mekel, Michal; Hyams, Gila; Horowitz, Nethanel A.; Gepstein, Vardit; Netzer, Itamar; Saban, Hagar Cohen; et al.
Abstract: Objectives: We evaluated the antibody response to the BNT162B2 vaccine among healthcare workers (HCWs) to identify factors associated with decreased immunogenicity. Methods: This prospective cohort study included consenting HCWs who completed a questionnaire regarding background illnesses, medications, and post-vaccination allergic reactions or rash. All HCWs were tested for anti-spike antibodies (LIAISON SARS-CoV-2 S1/S2 IgG assay) 1 and 3 months after the second vaccine dose. A multivariate mixed linear model was adjusted to participants' data and fit to predict antibody levels after the second BNT162B2 vaccine dose, based on antibody levels at 1 month and the slope between 3 months and 1 month. Multivariate analyses identified factors associated with lower antibody levels. Results: In total 1506 HCWs were tested for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) antibodies. Older age was associated with lower mean antibody levels (–1.22 AU/mL, p < 0.001, 95%CI –1.43 to –1.01). In addition, male sex (–22.16 AU/mL, p < 0.001, 95%CI –27.93 to –16.39), underlying condition (–10.86 AU/mL, p 0.007, 95%CI –18.81 to –2.91) and immunosuppressive treatment (–28.57 AU/mL, p 0.002, 95%CI –46.85 to –10.29) were associated with significantly lower mean antibody levels. Allergic reactions after vaccine administration or peri-vaccination glucocorticosteroid treatment were not correlated with antibody levels. Conclusions: Most HCWs had measurable antibodies at 3 months. Risk factors for lower antibody levels were older age, male sex, underlying condition, and immunosuppressive treatment. These factors may be considered when planning booster doses during vaccine shortages. Graphical abstract: Image 1